Parental involvement of immigrant parents in early educational centers and its relationship with intercultural sensitivity - Bilbao, Marian; Guglielmetti-Serrano, Florencia; Mera-Lemp, María José; Pizarro, José J.; Fernandez, Denisse; Martínez-Zelaya, Gonzalo (Frontiers in Psychology, 2025)
IntroductionEarly education centers play a crucial role in children’s development. Research shows this process is partly supported by parental involvement in activities promoted by these centers. Additionally, early education helps reduce disparities and fosters inclusion of disadvantaged groups, such as immigrant families. These families often face barriers for their involvement, including limited understanding of the local culture, and teachers’ awareness of their cultural backgrounds and expectations. Literature suggests that interculturally sensitive practices addressing families’ cultural and linguistic needs can foster more effective communication between parents and teachers. Intercultural sensitivity, the affective dimension of intercultural communication, is a personal capacity enabling individuals to recognize and accept cultural differences while identifying commonalities. Thus, enhancing intercultural sensitivity within the educational community may support greater immigrant parental involvement in their children’s education. This study examines the role of intercultural sensitivity in predicting immigrant parental involvement in early education in Chile.MethodsUsing a sample of 347 immigrant parents, we assessed parental involvement levels, intercultural sensitivity, and perceived facilitators and barriers to participation, with several sociodemographic variables.ResultsResults from multinomial logistic regression showed that higher intercultural sensitivity significantly predicted greater parental involvement in children’s educational activities. Parents with lower intercultural sensitivity were 75% more likely to report “almost never” participating than those with high intercultural sensitivity. The educational level also played a role, as parents with technical education were significantly less involved than those with university education. Among facilitators, a positive climate among parents increased the odds of always participating, while the presence of other immigrant families in school paradoxically correlated with lower involvement. Regarding barriers, parents who perceived that the school lacked a special approach for immigrant families were 3.79 times more likely to report low participation.DiscussionThese findings highlight the importance of fostering intercultural sensitivity in school communities to enhance immigrant parental engagement in early education. Implications for educational policy and practices promoting inclusive and culturally responsive environments are discussed.